Beta-band power modulation in the human amygdala during a Direct Reach arm reaching task - Jonathon Cavaleri; Shivani Sundaram; Roberto Martin Del Campo-Vera; Xiecheng Shao; Ryan S. Chung; Miguel Parra; Adith Swarup; Selena Zhang; Alexandra Kammen; Angad Gogia; Xenos Mason; Ryan McGinn; et al. (Neuroscience Research)
The human amygdala is primarily known for its involvement in processing emotional and fearful responses, but newer evidence has identified a role for this structure in motor processing. Our lab previously utilized an arm-reaching task and observed significant beta-band (13–30 Hz) modulation in the hippocampus. Given these results, we sought to characterize the role of beta-band modulation in the amygdala during movement execution in participants with stereoelectroencephalography (SEEG) depth electrodes in the amygdala for seizure localization. We show that 9 of 13 participants (69.2 %) showed decreased beta-band power in the amygdala during the Response (movement execution) phase of an arm-reaching task when compared to Fixation (baseline). Secondary analyses show that there are no statistically significant differences in beta-band modulation between ipsilateral and contralateral implanted electrodes, but there is a small difference between male and female participants. The decrease in beta-band power in the amygdala during the Response phase of a Direct Reach task is consistent with our previous findings in the hippocampus. Our study is the first to report beta-band modulation in the amygdala during motor processing and sets the stage for further studies into the involvement of the amygdala in motor control.